NEUROPSYCHOLOGICAL ASSESSMENT IN AUTISM SPECTRUM DISORDER THE NEUROPSYCHOLOGIST-INVESTIGATOR: BETWEEN HIDDEN COMPETENCE AND ANTI-IATROGENIC ETHICS - Narthagnan Chaves da Silva, Francisco (Health and Society, 2025)
Neuropsychological assessment (NA) is a central tool in the differential diagnosis of Autism Spectrum Disorder (ASD). However, this review and theoretical essay argues that the application of standardized psychometric instruments in Brazil faces severe methodological limitations, especially within the non-verbal population. Factors such as apraxia of speech, barriers in social reciprocity (rapport), and sensory overload often invalidate the measurement of constructs like the Intelligence Quotient (IQ), leading to false negatives of cognitive potential. This is illustrated by emblematic cases of non-verbal individuals (e.g., Jason Arday, Carly Fleischmann) erroneously diagnosed with Intellectual Disability. This article proposes that the solution to this gap lies not in waiting for new tests, but in a paradigm shift: the adoption of a “neuropsychologist-investigator” stance. Grounded in clinical praxis, the text calls on neuropsychologists to question themselves, observe critically, and develop procedural assessment methods that transcend psychometric rigidity, thereby avoiding diagnostic iatrogenesis.